Potensi Ekonomi dalam Pengelolaan Persampahan Berkelanjutan Kota Surabaya - Muhammad Ramadhani Miftahul Asa; Belinda Ulfa Aulia (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Waste management remains a critical challenge for many nations. The continuous increase in waste generation not only diminishes public space and disrupts human activities but also degrades the overall quality of life. Conversely, effectively managed waste can yield significant benefits. One of the primary frameworks in sustainable waste management is the Circular Economy a model that integrates economic systems with long-term environmental sustainability. This study, titled "Economic Potential in Sustainable Waste Management of Surabaya City," examines waste management in Surabaya, focusing specifically on solid waste sourced from Temporary Waste Collection Sites (TPS) and 3R Waste Treatment Facilities (TPS3R) across the city. Despite having 189 TPS locations scattered throughout the city, Surabaya still faces constraints regarding waste reduction. A literature review method was utilized and combined with data from the Environmental Agency of Surabaya City to formulate more effective waste management recommendations for Surabaya. By integrating Circular Economy principles, this research aims to quantify the economic potential of waste reduction in Surabaya. Surabaya generates approximately 1,800 tons of waste daily. Given that the Benowo Waste-to-Energy Plant (PLTSa) can only process 1,000 tons per day, a residual 800 tons of waste accumulates at the Benowo Landfill (TPA). Furthermore, while the national waste reduction target is set at 20% and Surabaya targeted 28% for the year 2022, the city has only achieved a reduction rate of 7.43%. This gap underscores the urgent need for a Circular Economy strategy or the leverage of economic potential from waste reduction to accelerate waste minimization. The analytical methods employed include Mass Balance Analysis to provide a comprehensive overview of waste processing and to calculate the volume of waste reduction and Life Cycle Costing (LCC) is utilized to measure and evaluate the economic potential and management of solid waste in Surabaya City. The results indicate that waste reduction can decrease waste management costs by 69%. The solid waste management cost before reduction is Rp 579,908,460/day, which significantly drops to Rp 180,098,802/day after implementation. By identifying the value of this waste reduction potential, it is expected that efforts to realize and optimize waste reduction in Surabaya City can be maximized